Mobile Mobile Web Based Al-Quran Index - Ichsan, Mochammad (Jurnal Saintekom : Sains, Teknologi, Komputer dan Manajemen, 2018)
Al-Qurâ€™an is a holy book of Muslims that is derived by Allah ï·» revealed to Rasulullah ï·º. Through an angelic messenger jibril with its pronunciation and meaning. Al-Qurâ€™an is a miracle that he is very valuable to Muslims to this day. The scriptures revealed in the holy month of Ramadan, contained guidance and guidance for mankind in achieving the happiness of life in the world and the hereafter. Al-Qurâ€™an was revealed to the Messenger Rasulullah ï·º to be used as guidelines, concepts, and rules of human life as the word of Allah ï·» â€œ Al-Qurâ€™an has no doubt about it; the guidance of those who fear Allah, those who believe in the Unseen, who establish the prayer, and spend of some of the sustenance which we bestow upon them.â€ (QS.al-Baqarah [2]: 2-3). Writing methods used in this study include data collection methods (interview method, literature method, documentation method, and experiment method) and system development methods.To facilitate Muslims in reading and knowing the Qur'an both meaning and content then the authors make a study with the title â€œMobile Web Based Al-Quran Indexâ€ this application will be used by the people in searching and finding suras and verses related to certain laws in the hope of getting the attention of the community because it better understand the meaning of the derivation of verses in the al-Qurâ€™an.this research has been successfully implemented an application dictionary isitlah biology android based by using php programming language and database which is based on Structured Query Language (SQL) is MySQL with name indekquran.sql with 4 tables the authors apply the method of software development waterfall.